2017
DOI: 10.2119/molmed.2016.00214
|View full text |Cite
|
Sign up to set email alerts
|

Dabigatran Potentiates Gemcitabine-Induced Growth Inhibition of Pancreatic Cancer in Mice

Abstract: Pancreatic cancer is one of the most lethal solid malignancies, with few treatment options. We have recently shown that expression of protease activated receptor (PAR)-1 in the tumor microenvironment drives the progression and induces the chemoresistance of pancreatic cancer. As thrombin is the prototypical PAR-1 agonist, here we address the effects of the direct thrombin inhibitor dabigatran on pancreatic cancer growth and drug resistance in an orthotropic pancreatic cancer model. We show that dabigatran trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
(68 reference statements)
3
21
0
Order By: Relevance
“…n.descr., not described in paper; no., number; i.p., intraperitoneal; i.v., intravenous; s.c., subcutaneous. [29][30][31][32], two studies reported on rivaroxaban (both 2019) [24,25], and one study reported on both dabigatran etexilate and rivaroxaban (2019) [23].…”
Section: Study Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…n.descr., not described in paper; no., number; i.p., intraperitoneal; i.v., intravenous; s.c., subcutaneous. [29][30][31][32], two studies reported on rivaroxaban (both 2019) [24,25], and one study reported on both dabigatran etexilate and rivaroxaban (2019) [23].…”
Section: Study Selectionmentioning
confidence: 99%
“…The 9 selected publications included a total of 19 in vivo experiments (Table 1). Experiments were conducted in mice (n = 18) or rats (n = 1) of both male and female sex; and included carcinogenicity studies [28], spontaneous breast cancer [24], subcutaneous (fibrosarcoma [24], colorectal [24] and pancreatic cancer [25]), orthotopic (pancreatic [28,32] and breast cancer [29,31,23]) and experimental metastasis models (melanoma [27] and ovarian cancer [30]). The number of animals per treatment group ranged from 4 to 50.…”
Section: Description Of the Included Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 An additional study has reported that dabigatran potentiates gemcitabine-induced growth inhibition of pancreatic cancer but does not affect primary tumor growth when used as monotherapy. 19 Similar to the abovedelineated anticoagulants, apixaban used at a high dose (five times the therapeutic dose) has been found to interfere with cancer cell function in vitro, reducing proliferation and increasing apoptosis in several cancer cell lines. 20 Previously published data demonstrated a favorable effect of warfarin on survival of patients with non-small cell lung cancer, although such effect was not found in other investigated malignancies, including colon, prostate, and head and neck cancers.…”
Section: Antitumor Effects Of Direct Oral Anticoagulantsmentioning
confidence: 99%